Erythromycin inhibits prostaglandin F2?-induced contractions of myometrium isolated from non-pregnant rats - Celik, H; Ayar, A; Baltaci, A; Tug, N (Elsevier Science Bv, 2002)
Objective The aim of this study was to investigate the effects of erythromycin on prostaglandin F-2alpha (PGF(2alpha))-induced contractions of isolated myometrial strips from non-pregnant rats. Design In vitro pharmacological study. Setting Firat University Faculty of Medicine. Sample Myometrium samples were taken from 55 adult Wistar rats. Methods Myometrial strips were isolated from mature, non-pregnant Wistar rats. Isometric contractions of these strips were induced with 1 muM PGF(2alpha). Effects of 0.01, 0.1, 0.2, 0.5 and 1 mM erythromycin on the frequency and amplitude of these PGF(2alpha)-induced contractions were recorded. Main outcome measures The inhibition of prostaglandin F-2alpha-induced contractions in vitro. Results Application of 0.01 mM erythromycin had no effect on either amplitude or frequency of contractions. However, 0.1, 0.2, 0.5 and 1 mM erythromycin decreased the frequency and amplitude of PGF(2alpha)-induced contractions. The inhibitory effect of erythromycin on amplitude was 27%, 38%, 54% and 83% (P < 0.05), and that on frequency was 10%, 16%, 32% and 61% (P < 0.05) at 0.1, 0.2, 0.5 and 1 mM concentrations, respectively. Conclusion The results of this study demonstrate that erythromycin inhibits PGF(2alpha)-induced contractions in rat myometrium. Because PGF(2alpha)-induced contractions have been suggested to be involved in the pathogenesis of primary dysmenorrhoea, effects of erythromycin in this clinical entity may present a new approach for the treatment.
Keywords: Primary Dysmenorrhea; Preterm Labor; Women; Muscle; Metabolites; Fluid